Novel Ferrofluids Coated with a Renewable Material Obtained from Cashew Nut Shell Liquid - Casagrande-Denardin, J (2012)
In this work, we present the synthesis and characterization of a new surfactant molecule obtained from a byproduct of the cashew nut processing (diphosphorylated cardol, DPC). It is herein used to overcoat magnetic nanoparticles showing spinel structures in order to create new ferrofluids. The nanoparticle structure and magnetic properties have been deeply investigated. DPC-functionalized Fe 3O 4 and NiFe 2O 4 samples exhibit higher magnetic saturation than DPC-CoFe 2O 4. These new ferrofluids reveal appealing as possible nanoparticle stabilizing molecules, magnetic resonance imaging agents, storage systems or in any material science field that requires the employment of biocompatible magnetic stable fluids. © Springer-Verlag 2011.